2017
DOI: 10.3390/antib6040015
|View full text |Cite|
|
Sign up to set email alerts
|

Antibody Selection for Cancer Target Validation of FSH-Receptor in Immunohistochemical Settings

Abstract: Background: The follicle-stimulating hormone (FSH)-receptor (FSHR) has been reported to be an attractive target for antibody therapy in human cancer. However, divergent immunohistochemical (IHC) findings have been reported for FSHR expression in tumor tissues, which could be due to the specificity of the antibodies used. Methods: Three frequently used antibodies (sc-7798, sc-13935, and FSHR323) were validated for their suitability in an immunohistochemical study for FSHR expression in different tissues. As qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 43 publications
0
15
1
1
Order By: Relevance
“…Basic information on selected popular FSHR antibodies is listed in Table 1A. The specificity of two frequently used antibodies, sc-7798 and sc-13935, from Santa Cruz Biotechnology, has been recently revisited (47). In a comprehensive study, the authors compared these antibodies with FSHR323 (44) and two potential therapeutic anti-hFSHRs Ylanthia® antibodies (Y010913, Y010916) for their suitability in IHC detection of FSHR expression in various tissues (47).…”
Section: Anti-fshr Antibodiesmentioning
confidence: 99%
“…Basic information on selected popular FSHR antibodies is listed in Table 1A. The specificity of two frequently used antibodies, sc-7798 and sc-13935, from Santa Cruz Biotechnology, has been recently revisited (47). In a comprehensive study, the authors compared these antibodies with FSHR323 (44) and two potential therapeutic anti-hFSHRs Ylanthia® antibodies (Y010913, Y010916) for their suitability in IHC detection of FSHR expression in various tissues (47).…”
Section: Anti-fshr Antibodiesmentioning
confidence: 99%
“…Moreover, FSH, LH, and hCG were shown to enhance several cytokines from the human peripheral blood mononuclear cells in vitro. The above concerns interferon-gamma [47], interleukin-6 [48], interleukin Pawlikowski et al [19] revealed immunopositivity with anti-FSHR antibody in human non-neoplastic adrenal cortex as well as in benign and malignant adrenal tumours; however, the specificity of this immunoreaction is still under discussion [20] Nervous system One of the earliest findings of the direct action of gonadotropins on the nervous system was the observation of degenerative changes in autonomic gangliocytes after FSH or LH administration in hypophysectomised-gonadectomised rats [1]. Further evidence of the direct gonadotropin action of either LH or FSH on neurons was the discovery of "short" feedback loops in the control of gonadotropin secretion.…”
Section: Immune Systemmentioning
confidence: 99%
“…Innym dowodem bezpośredniego działania LH lub FSH na neurony było odkrycie "krótkiej" pętli sprzężenia zwrotnego w kontroli wydzielania gonadotropin. Wykazano mianowicie, że implantacja LH [19] lub FSH [20] do wyniosłości pośrodkowej prowadzi do spadku wydzielania odpowiednich hormonów przypuszczalnie przez zahamowanie neuronów podwzgórzowych produkujących GnRH. Wykazano także, że LH moduluje także aktywność hipokampa u szczura [21].…”
Section: Układ Nerwowyunclassified
“…
The authors wish to make the following correction to the Conflict of Interests section in their published paper [1]:"Christian Kunz and Solveig Peters are employees and Nina Möker and Robert Rauchenberger are former employees of MorphoSys AG, which owns the Ylanthia antibodies described in the publication. "

The manuscript will be updated and the original will remain online on the article webpage.

…”
mentioning
confidence: 99%
“…The authors wish to make the following correction to the Conflict of Interests section in their published paper [1]:…”
mentioning
confidence: 99%